Personalized Scaffolds for Diabetic Foot Ulcer Healing Using Extracellular Matrix from Induced Pluripotent Stem‐Reprogrammed Patient Cells. Issue 10 (14th September 2022) - Santarella, Francesco; do Amaral, Ronaldo Jose Farias Correa; Lemoine, Mark; Kelly, Domhnall; Cavanagh, Brenton; Marinkovic, Milica; Smith, Avi; Garlick, Jonathan; O'Brien, Fergal J.; Kearney, Cathal J.
Abstract : Diabetic foot ulcers (DFUs) are chronic wounds sustained by pathological fibroblasts and aberrant extracellular matrix (ECM). Porous collagen‐based scaffolds (CS) have shown clinical promise for treating DFUs but may benefit from functional enhancements. Our previous work showed fibroblasts differentiated from induced pluripotent stem cells are an effective source of new ECM mimicking fetal matrix, which notably promotes scar‐free healing. Likewise, functionalizing CS with this rejuvenated ECM shows potential for DFU healing. Herein, an approach to DFU healing is demonstrated for the first time using biopsied cells from DFU patients, reprogramming those cells, and functionalizing CS with patient‐specific ECM as a personalized acellular tissue‐engineered scaffold. A two‐pronged approach is taken: 1) direct ECM blending into scaffold fabrication, and 2) seeding scaffolds with reprogrammed fibroblasts for ECM deposition followed by decellularization. The decellularization approach reduces cell number requirements and maintains naturally deposited ECM proteins. Both approaches show enhanced ECM deposition from DFU fibroblasts. Decellularized scaffolds additionally enhance glycosaminoglycan deposition and subsequent vascularization. Finally, reprogrammed ECM scaffolds from patient‐matched DFU fibroblasts outperform those from healthy fibroblasts in several metrics, suggesting ECM is in fact able to redirect resident pathological fibroblasts in DFUs toward healing, and a patient‐specific ECM signature may be beneficial. Abstract : Herein, a blended and a decellularized scaffold starting from extracellular matrix produced by rejuvenated fibroblasts, which are derived by iPSC reprogramming of DFU patient cells, is produced for the first time. Beneficial matrix is deposited on the scaffolds following seeding of patient‐matched pathological fibroblasts.